Erasmus, Contarini, and the religious republic of letters - Furey, Constance M. (Cambridge Univ. Press, 2006)
Introduction -- A new kind of religious life -- Creating an alternative community -- The spirited quest -- Necessary relationships -- Defining the ideal -- Epilogue